2006
DOI: 10.1111/j.1747-0765.2006.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basal side-dressing of various types of coated urea fertilizer on shoot growth, yield components and seed composition of soybean (Glycine max(L.) Merr.)

Abstract: Effect of basal side-dressing ORIGINAL ARTICLE Effect of basal side-dressing of various types of coated urea fertilizer on shoot growth, yield components and seed composition of soybean (Glycine max (L.) Merr.) Yoshihiko AbstractApplication of nitrogen (N) fertilizer at different times affected the shoot characters, yield components and seed composition of the soybean cultivar "Enrei" and its non-nodulating line "En1282". Soybean plants were cultivated using various types of coated urea fertilizers for cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Top dressing of N fertilizer sometimes gives positive effects on seed yield, but results are not consistent. Takahashi et al reported the effect of basal side-dressings of various types of controlled release nitrogen fertilizer (coated urea) on shoot growth and seed yield of soybean [73]. The yield was significantly higher in all the coated urea basal side-dressing treatments compared with control, particularly in CUS120 which releases urea from 60 to 120 days after planting with a sigmoid pattern of N release.…”
Section: A New Fertilization Technique To Promote Nitrogen Fixation Amentioning
confidence: 99%
“…Top dressing of N fertilizer sometimes gives positive effects on seed yield, but results are not consistent. Takahashi et al reported the effect of basal side-dressings of various types of controlled release nitrogen fertilizer (coated urea) on shoot growth and seed yield of soybean [73]. The yield was significantly higher in all the coated urea basal side-dressing treatments compared with control, particularly in CUS120 which releases urea from 60 to 120 days after planting with a sigmoid pattern of N release.…”
Section: A New Fertilization Technique To Promote Nitrogen Fixation Amentioning
confidence: 99%